Kristus algoritmik: Kecerdasan buatan, teologi digital, dan masa depan diskursus Kristologi - Daud Darmadi (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
This study investigates the intersection of advances in artificial intelligence technology and contemporary Christology through the concept of the